To study the prevalence of metabolic-associated fatty liver disease in a tertiary hospital in Bundelkhand region - Neha Rathore,; Kuldeep Chandel,; Ajeet Singh,; Aniket Ashok Satale,; Gaurav Singh, (Asian Journal of Medical Sciences, 2025)
Background: Metabolic-associated fatty liver disease (MAFLD) is a growing global health concern associated with metabolic dysfunction, including obesity, type 2 diabetes mellitus, and dyslipidemia. Its prevalence is increasing, particularly in developing regions, necessitating early detection and intervention. Aims and Objectives: This study aims to determine the prevalence of MAFLD in a tertiary care hospital and assess the demographic profile and associated risk factors in the Bundelkhand region. Materials and Methods: A cross-sectional study was conducted in the Department of General Medicine, Maharani Laxmi Bai Medical College, Jhansi, from June 2023 to June 2024, including 302 patients attending outpatient and inpatient services. Participants underwent clinical evaluations, biochemical tests, and ultrasonography to diagnose MAFLD. Risk factors such as obesity, hypertension, diabetes, and dyslipidemia were analyzed. Statistical tests were applied to assess significant associations. Results: The prevalence of MAFLD was 54.63%, with a higher incidence in males (median age: 50 years) than females (48 years). Among MAFLD patients, obesity (81.81%), type 2 diabetes (46.06%), metabolic syndrome (82.42%), dyslipidemia (66.06%), hypothyroidism (37.57%), and hypertension (37.57%) were significantly prevalent (P<0.05). Liver function tests and biochemical markers were significantly altered in MAFLD cases. Conclusion: The study highlights a high prevalence of MAFLD in the Bundelkhand region, closely linked to metabolic risk factors. Early screening and lifestyle interventions are crucial to prevent disease progression.